“WHAT’S A LEADER WITHOUT TRUST?”: PERCEPTIONS OF UNETHICAL LEADERSHIP AND LOSS OF TRUST FROM THE EXPERIENCES OF MENA REFUGEE AND IMMIGRANT WOMEN. - Luethke, Tiffani N. (Journal of Ethnographic & Qualitative Research, 2021)
This ethnographic study advances understanding of follower perceptions of leadership through an intersectional approach, based on the experiences of Middle Eastern and North African (MENA) immigrant and refugee women following resettlement in the United States. The findings discussed support follower perceptions of unethical leadership among government entities based on the pre-migration context of the participants’ home countries. This research is part of a larger study involving three years of immersive observations during weekly classes, three focus group sessions, and 30 interviews with key informants, from which five major findings related to leadership emerged. In the present article, the findings related to unethical leadership are presented with its themes of corruption, deceit, egotism, inaccessibility, theft, and loss of trust.